Storage strategies and processing of bovine milk samples for pregnancy-associated glycoproteins detection test - Silva, H. K. da; Cassoli, L. D.; Pantoja, J. C. F. [UNESP]; Cerqueira, P. H. R.; Winckler, J. P. P.; Coitinho, T. B.; Machado, P. F. (Taylor & Francis As, 2017)
Three experiments were performed to test if the time and storage conditions of milk samples, the preheating of samples in a water bath, as well as the carryover effect in laboratory analysis equipment could affect the pregnancy-associated glycoproteins (PAG) levels, and consequently the results of a pregnancy test. The pregnancy test used in both experiments uses the enzyme-linked immunosorbent assay method to measure the concentrations of PAG and classify the samples as pregnant, nonpregnant or suspicious. As a result, PAG levels showed no variation when the samples were analyzed up to 9 days after collection, whether stored in ambient temperature or refrigerated. The preheating of the samples in a water bath and prior to the analysis of SCC and composition also did not affect the levels of PAG, allowing the same sample used in the quality analysis to be used for the pregnancy test.
Keywords: Carryover effect; milk sample; pregnancy test; sample age; storage conditions; water bath